2016
DOI: 10.1080/15475441.2016.1232651
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Rapid Naming Predict Chinese Word Reading?

Abstract: We are grateful to the children and parents for their participation and school staff for their support. This research was supported by funding from the University of Hong Kong (awarded to Au). We sincerely thank several cohorts of research assistants and interns for their help in this project. AbstractRapid automatized naming (RAN) robustly predicts early reading abilities across languages, but its underlying mechanism remains unclear. This study found that RAN associated significantly with processing speed bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This subtest from HKT-P(III) measured rapid automatized naming of highly familiar visual stimuli, a task that closely predicts literacy performance across difference languages 68 . The participants were presented with a matrix of 8 rows of 5 digits arranged in random sequences, and were instructed to name aloud the digits in serial order as quickly and as accurately as possible.…”
Section: Methodsmentioning
confidence: 99%
“…This subtest from HKT-P(III) measured rapid automatized naming of highly familiar visual stimuli, a task that closely predicts literacy performance across difference languages 68 . The participants were presented with a matrix of 8 rows of 5 digits arranged in random sequences, and were instructed to name aloud the digits in serial order as quickly and as accurately as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Frequently assessed with the rapid number naming task, rapid automatized naming (RAN) is a good predictor of reading ability (Kirby et al, 2010;Liao et al, 2015;Norton and Wolf, 2012;Shum and Au, 2017), and recent studies have shown that RAN is related to Chinese orthographic processing (Liao et al, 2015;Wang et al, 2018). Morphological awareness is another reliable predictor of dyslexia in Chinese (Lei et al, 2011;Li et al, 2009;Shu et al, 2006).…”
Section: Mst Metrics and Reading-related Cognitive Skillsmentioning
confidence: 99%